Factors Affecting Interdialytic Weight Gain (IDWG) in Kidney Failure - Lia Murdaningsih; Wenny Trisnaningtyas; Nina Indriyawati (JENDELA NURSING JOURNAL, 2023)
Background: interdialytic Weight Gain (IDWG) is a parameter easily measured routinely at the beginning of a dialysis session and an essential indicator to recommend fluid intake for patients with kidney failure. Increased IDWG is associated with various complications in patients undergoing hemodialysis.Purpose: to analyze the factors that influence IDGW in hemodialysis patients.Methods: a cross-sectional design was used in this study. Data were collected during January-March 2022. Data collected included: demographic variable (gender, age, level of education, fluid intake, thirst, and stress)/ Data were analyzed with descriptive correlation statistic, Simple regression analysis ANOVA.Results: the total number of participants recruited was 65 participants who undergoing hemodialysis 1 month at a private hospital in Semarang, there were 27 participants (41.5%) in the moderate IDGW category, and 20 participants (30.8%) experienced severe stress, while fluid intake had an influence on IDGW (r=0.493, p=0.000), thirst (r=0.394, p=0.001) and stress (r=0.562, p=0.000).Conclusion: in this study, the factors associated with IDWG were fluid intake, thirst and stress. The previous 3 factors significantly increased IDWG due to decreased renal function, but increased fluid intake interfered with patient compliance, including fluid management and hemodialysis. Factors not included in IDWG include age, gender and education.